Теоретичні аспекти вдосконалення професійної підготовки майбутніх фахівців туристичної галузі в Україні - Біда Олена; Bida Olena; Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána; Сироєжко Ольга; Syroiezhko Olha; Богів Евеліна; Bohiv Evelina (Видавництво «Код», 2023)
Резюме. У статі доведено необхідність вивчення теоретичних аспектів, дослідження питань оптимізації та вдосконалення професійної підготовки майбутніх фахівців з туризму в Україні, що є значущою та актуальною проблемою на сьогодні. Обґрунтувано необхідність формування кроскультурної компетентності при підготовці майбутніх фахівців туристичної галузі. Розкрито головну професійну якістю сучасного фахівця туристичної галузі. Виокремлено пріоритетне завдання професійної підготовки майбутніх фахівців з туризму.

Abstract. The necessity of studying theoretical aspects, researching issues of optimization and improvement of professional training of future specialists in tourism in Ukraine, which is a significant and relevant problem today, has been proven. The need for the formation of cross-cultural competence in the training of future specialists in the tourism industry is substantiated. The main professional quality of a modern specialist in the tourism industry is revealed. The priority task of the professional training of future tourism specialists is the formation of a future specialist with a strategic way of thinking, professional knowledge in the field of tourism, able to identify and solve complex professional tasks and practical problems. The mechanism of professional activity makes it possible to realize in practice the systematic integration of activity, person-oriented and competence-based approaches, which, with the clear development of the main types of activities in the form of professional tasks and personal qualities, taking into account the prospects for the development of the economic sector, will ensure the formation of professional competence, motivation for learning and quick adaptation of graduates of higher education institutions in the tourism industry. The main factors influencing the level of practical training of students are highlighted: training technology; professional and cognitive interest and professional orientation of the student’s personality, his value orientations; cognitive and communicative abilities of students; content, forms and methods of practical training; professional competence of teachers; family, family traditions. The main criteria of readiness for professional activity of tourism industry specialists are grouped: professional awareness, independence of emotional positive attitude towards tourism activity, speed of personal adaptation in various production situations, expediency of practical actions, level of formation of organizational skills, mastery of interpersonal communication techniques, etc. The tasks that must be solved during the training of future tourism specialists are listed: training of a competitive specialist; formation of the desire to achieve a high level of professionalism; improvement of professional training based on modern innovative technologies; formation of cross-cultural competence, development of initiative and creative activity of future specialists on the basis of partnership relations; development of tolerance, culture of communication and behavior in intercultural professional interaction.
Theoretical aspects of improving the professional training of future specialists in the tourism industry in Ukraine
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00011317
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-3
Keywords: професійна підготовка; майбутні фахівці; туристична галузь; Україна; критерії готовності до професійної діяльності фахівців туристської індустрії; фактори впливу на рівень практичної підготовки студентів